Reflections on theoretical framework use in nursing research - Maria Ribeiro Lacerda; Rudval Souza da Silva; Nadirlene Pereira Gomes; Silvana Regina Rossi Kissula Souza (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to reflect on theoretical framework use in nursing research. Methods: a theoretical-reflexive study, based on concepts and constructs pertinent to using nursing theories and other sciences, considering issues of epistemology or philosophy of science. Results: we presented what it is and why to do nursing research and what a theoretical framework is and why to use it, in addition to some considerations regarding theoretical framework use in nursing research, essential for constructing disciplinary knowledge, which enables the materialization of researchers' work and the presentation of propositions resulting from investigations in and for nursing as a discipline and science. Final Considerations: based on a reflection based on epistemological conceptions, it is possible to affirm that a theoretical framework is the core of researchers' thinking, delimiting a problem to be investigated and, based on it, outlining methodological strategies to be followed, supporting nursing action and thinking as discipline and science.